Connecting vehicles using Li-Fi technology for reducing accidents - Raghava Rao, K; Sai Sasi Preetham, K; Edukondalu, K; V.Ragavendra Reddy, L (International Journal of Engineering and Technology, 2018)
Li-FI technology is transferring of data using Led’s in visible light spectrum. Basically Li-Fi is similar to that of Wi-Fi but this Li-Fi is 10 times faster than Wi-Fi, as Wi-Fi uses radio frequency which has some transmission limitation Li-Fi is very useful to replace such limitations. We can use this technology in many areas like hospitals air traffic control, vehicles and under water communications.in this Li-Fi technology we mainly use led’s as a transmitter which will send stream of data by toggling with a speed that can’t be identified by the human eye and photodiode as a receiver which converts light energy to electrical energy. Connecting vehicles can be obtained by replacing head and tail lamps of the vehicle with led’s and photodiode should be attached at both front and rear end of the vehicle go get the data from both leading and following vehicles. By transferring the data about the motion of vehicle through led’s we can reduce the collision of vehicles. This technology is also used to regulate the information about the traffic by replacing the street lights with led and transfer data about the traffic in that route for every vehicle that passes through.